Septic coronary embolism – A case report (Indian Journal of Case Reports, 2016)
The embolization represents one of the most dreadful complications of infective endocarditis; however, coronary embolism is a rare entity with an incidence of 2.9%. The definite line of management is rather ambiguous in published literatures. We reported an urgent coronary revascularization with double valve replacement due to infective endocarditis with large vegetation complicated by coronary embolism and acute coronary syndrome.